Defining Benchmark Outcomes for Pancreatoduodenectomy With Portomesenteric Venous Resection. Issue 5 (November 2020) - Raptis, Dimitri A.; Sánchez-Velázquez, Patricia; Machairas, Nikolaos; Sauvanet, Alain; Rueda de Leon, Alexandra; Oba, Atsushi; Groot Koerkamp, Bas; Lovasik, Brendan; Chan, Carlos; Yeo, Charles J.; Bassi, Claudio; Ferrone, Cristina R.; et al.
Abstract : Objective: The aim of this study was to establish clinically relevant outcome benchmark values using criteria for pancreatoduodenectomy (PD) with portomesenteric venous resection (PVR) from a low-risk cohort managed in high-volume centers. Summary Background Data: PD with PVR is regarded as the standard of care in patients with cancer involvement of the portomesenteric venous axis. There are, however, no benchmark outcome indicators for this population which hampers comparisons of patients undergoing PD with and without PVR resection. Methods: This multicenter study analyzed patients undergoing PD with any type of PVR in 23 high-volume centers from 2009 to 2018. Nineteen outcome benchmarks were established in low-risk patients, defined as the 75th percentile of the median outcome values of the centers (NCT04053998). Results: Out of 1462 patients with PD and PVR, 840 (58%) formed the benchmark cohort, with a mean age was 64 (SD11) years, 413 (49%) were females. Benchmark cutoffs, among others, were calculated as follows: Clinically relevant pancreatic fistula rate (International Study Group of Pancreatic Surgery): ⩽14%; in-hospital mortality rate: ⩽4%; major complication rate Grade≥3 and the CCI up to 6 months postoperatively: ⩽36% and ⩽26, respectively; portal vein thrombosis rate: ⩽14% and 5-year survival for patients with pancreatic ductal adenocarcinoma: ≥9%. Conclusion: These novel benchmark cutoffs targeting surgical performance, morbidity, mortality, and oncological parameters show relatively inferior results in patients undergoing vascular resection because of involvement of the portomesenteric venous axis. These benchmark values however can be used to conclusively assess the results of different centers or surgeons operating on this high-risk group. Abstract : Supplemental Digital Content is available in the text